The Effect of Emotional Intelligence on Elementary School Students’ Mathematics Learning Outcomes: A Literature Review - Andi Asmia Sary; Harni Bukran; Ratri Pramudita (PT. Lontara Digitech Indonesia, 2025)
Emotional intelligence in mathematics learning refers to the ability to control one’s own emotions, manage them, and express emotions toward others. Emotional intelligence is highly necessary for understanding the lessons delivered by the teacher. This study aims to determine whether there is a positive effect of emotional intelligence on mathematics learning outcomes. This study used a qualitative approach obtained through a literature review. Based on several literatures and studies conducted on emotional intelligence, there is a positive effect on students’ mathematics learning outcomes. Emotional intelligence can be considered to contribute to students’ mathematics learning outcomes